Poetic justice and legal fictions - Kertzer, Jonathan 1946- (Cambridge University Press, 2010)
Literature reveals the intense efforts of moral imagination required to articulate what justice is and how it might be satisfied. Examining a wide variety of texts including Shakespeare's plays, Gilbert and Sullivan's operas, and modernist poetics, Poetic Justice and Legal Fictions explores how literary laws and values illuminate and challenge the jurisdiction of justice and the law. Jonathan Kertzer examines how justice is articulated by its command of, or submission to, time, nature, singularity, truth, transcendence and sacrifice, marking the distance between the promise of justice to satisfy our moral and sociable needs and its failure to do so. Poetic Justice and Legal Fictions will be invaluable reading for scholars of the law within literature and amongst modernist and twentieth century literature specialists --Provided by publisher.